2006
DOI: 10.2139/ssrn.893035
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Extreme Events: An Assessment of Economic Implications

Abstract: We use a dynamic general equilibrium model of the world economy to assess the economic implications of vulnerability from extreme meteorological events. In particular, we consider the impact of climate change on ENSO and NAO circulation patterns, and the implied variation on regional expected damages. Two effects are taken into account: (1) short-term impacts, due to changes in the demand structure, generated by higher/lower precautionary saving, and (2) variations in the regional economic growth paths.JEL Cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…However, the theory of precautionary saving argues that saving does not only serve to spread income over the life cycle, but might also serve as insurance against uncertain events (Lusardi 1998). In this context, Roson, Calzadilla and Pauli (2005) argue that individuals might react to natural disasters by increasing their savings. Based on a theoretical model of constant absolute risk aversion, Freeman, Keen and Mani (2003) show that the optimal amount of precautionary saving depends positively on expected loss, and thus on both the disaster probability and disaster loss.…”
Section: Transmission Channelsmentioning
confidence: 99%
“…However, the theory of precautionary saving argues that saving does not only serve to spread income over the life cycle, but might also serve as insurance against uncertain events (Lusardi 1998). In this context, Roson, Calzadilla and Pauli (2005) argue that individuals might react to natural disasters by increasing their savings. Based on a theoretical model of constant absolute risk aversion, Freeman, Keen and Mani (2003) show that the optimal amount of precautionary saving depends positively on expected loss, and thus on both the disaster probability and disaster loss.…”
Section: Transmission Channelsmentioning
confidence: 99%
“…The Computable General Equilibrium (CGE) Model describes equilibrium resource allocations and growth paths (Bergman and Henrekson, 2003). A CGE has been used to model present and future climate impacts on an economy (Roson, Calzadilla and Pauli, 2006). The method also has been applied as a spatially-specified CGE multi-regional infrastructure model to compare alternative investments in a South Korean highway network (Kim and Hewings (2003).…”
Section: Constraintsmentioning
confidence: 99%
“…To account for the impact of a disaster, one must estimate the effects on human resources, physical (built) capital, infrastructure, land endowments (natural capital), and productivity (Roson, Calzadilla and Pauli, 2006;Wiener, 2009). This accounting comprises three components:…”
Section: Constraintsmentioning
confidence: 99%
“…Akram (2012) projects that change in temperature, precipitation, and population growth have negative impact on economic growth of selected South Asian countries which are more vulnerable to climate changes including their socio-economic, demographic backgrounds, geo-climatic conditions, rural sector for livelihood and dependence on agriculture (Yohe et al, 2008). Roson et al (2006), Kumar et al, (2004) and Gbetibouo and Hassan (2005) suggested that rainfall, sea level pressure and temperature significantly influence the crop production. Ciscaret et al, (2010), Schlenker andRoberts (2009) and suggested that changes in climatic condition significantly affect the land use pattern such as conversion of forest land to pasture land and increased deforestation.…”
Section: Introductionmentioning
confidence: 99%